Population Programs : Facilitating Implementation at the Grassroots - World Bank (Washington, DC, 2012)
The population growth rate in Sub-Saharan Africa (SSA), at 2.7 per cent per year, is one of the highest in the world. This high growth rate tends to offset reductions in the number of poor in most SSA countries, as the rate of population increase is higher among the poor than the non-poor. The birth rate remains high because the fertility rate (average number of births per woman) remains exceptionally high at more than 6. However, only in a few SSA countries have population control and family planning programs produced tangible results. Often, this has been because the programs have not been fully accepted by the intended beneficiaries. Innovative and inclusive approaches that bring in all identifiable stakeholders at all stages of project and program development are obviously vital to achieving any real success on the ground.